The influence of thermal interaction on energy harvesting efficiency of geothermal piles in a group - Tiwari, Arvind Kumar; Kumar, Arvind; Basu, Prasenjit (Applied thermal engineering, 2022)
•Multiphysics analyses quantify group thermal interaction for geothermal piles.•Proposed power reduction factor quantifies loss in energy harvesting efficiency.•Sustained thermal operation and small pile spacing reduce group power output.•Pile diameter and circulation tube orientation do not affect thermal interaction.•Non-uniform placement of geothermal piles causes uneven temperature increments. This paper employs coupled multiphysics modelling of pile-soil heat exchange to quantify pile thermal interaction and its influence in diminishing the power output expected from a group of geothermal piles. Three-dimensional finite element models, which account for the flow of heat carrier fluid through the circulation tubes and conductive heat transport in pile and soil, are developed for different group arrangements of geothermal piles. Finite element analyses (FEAs) of a pair of geothermal piles reveal the effects of spacing, diameter, orientation of embedded fluid circulation tubes, and thermal operation time of geothermal piles on thermal interaction between the piles. A simple analysis-based expression is proposed to calculate power reduction factor that quantifies thermal interaction between two simultaneously acting geothermal piles. The proposed factor is further employed, in conjunction with the principle of superposition, to estimate power output from a group of geothermal piles. Comparison of predictions using the proposed method with FEA results suggests that the proposed method can successfully predict total energy harvesting efficiency (i.e., power output) of a thermally interacting group of geothermal piles.